Forex Market in Turkey - Öztürk, Ebru (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Foreign exchange market (FOREX) is the biggest volume financial market in the world. Through FOREX, one currency of a country is exchanged for another country’s currency. Since it is the world’s largest financial market, overall estimated daily average turnover of upwards is about $5.1 trillion. With the extend of globalization, both developing and developed countries have started to use similar policies among which financial liberalization is one of them. Financial liberalization is opening up economies to international capital flows, in particular by restructuring regulation of developing countries where controls and restrictions are either reduced or removed in order to attract international financial activities of developed countries to their own countries. In this study, analysis was done for Turkey’s position in the world; specifically, for the period before and after Capital Market Boards regulation. The new regulation creates authority to brokers. In order to compare the effect of changing legal structure on the participants of forex market, the groups of years were separated as the selected values of the year of 2012 before and after. The results of independent test were carried out. In conclusion, after the comparison of the parameters, the change in legal structure has significantly led to expansion in forex transactions. Test results for transactions in forex market shows that EUR/USD transactions have significantly increased after the regulation. In addition, the increase in the participation of both local and foreign investors after the regulation has also found to be statistically significant. Keywords: Forex, Forex Markets, Regulation and Legal Changes, Turkey.

ÖZ: Döviz piyasası (FOREX) dünyadaki en büyük hacme sahip finansal piyasasıdır. FOREX döviz kuru sistemi ile bir ülkenin bir para birimi başka ülkenin para birimi karşılığında değiştirilir. Genel olarak günlük ortalama cirosu yaklaşık 5,1 trilyon dolara ulaşarak, dünyanın en büyük finansal piyasasını oluşturmaktadır. Küreselleşmenin yaygınlaşması ile hem gelişmekte olan ülkeler hem de gelişmiş ülkeler benzer politikalar kullanmaya başlamıştır ki bunlardan birisi de ekonomileri uluslararası sermaye akışlarına açma sürecinde olan finansal liberalizasyon politikalarıdır. Bu politikalar özellikle gelişmekte olan ülkelerin, ya da gelişmiş ülkelerin uluslararası finansal faaliyetlerini kendi ülkelerine çekmek için finansal sistem üzerindeki kontrol ve kısıtlamaları azaltmak amacıyla uygulanmaktadır. Bu çalışmanın içeriği Türkiye'nin dünyadaki konumu ve özellikle Sermaye Piyasası Kurulu düzenlemeleri ile öncesi ve sonrası etkilerini ve düzenlemelerini incelemektir. Değişen yasal yapının forex pazarı katılımcıları üzerindeki etkisini karşılaştırmak için, yıl grupları, 2012 yılının öncesi ve sonrasında belirlenmiş değerler olarak ayrıldı. Sonuç olarak, parametrelerin karşılaştırılmasından sonra, yasal yapıdaki değişikliklerde önemli ölçüde forex market işleminin kullanılmasına başvurulduğu gözlemlenmiştir. Forex piyasalarındaki işlemler için uygulanan testte EURO/DOLAR işlemlerinin regülasyon sonrası önemli bir oranda artış gösterdiği gözlemlenmiştir. Piyasadaki katılımcılar için uygulanan testte ise hem yerel hem de yabancı katılımcıların regülasyon sonrası daha fazla piyasaya dahil oldukları test edilmiş ve istatistiksel olarak anlamlı bulunmuştur. Anahtar Kelimeler: Döviz alım satımı, Döviz Alım Satım Piyasası, Yasal Düzenlemeler, Türkiye
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2017. Supervisor: Prof. Dr. Mustafa Besim.
Keywords: Banking and Finance; Foreign exchange market-Turkey; Forex; Forex Markets; Regulation and Legal Changes; Turkey